Stdents’ Perception On The Need For The Development Of M-Learning Model For Teaching Arabic Reading Skills To Non-Arab Speakers. - Dulaym Alotaibi, Faihan; Siraj, Saeedah; Said Ismail, Wail Muil Alhaj (Opción, 2019)
Information technology is a powerful tool in enhancing and improving education system especially in the 20th century. Today, educational institutions adopted the use of various ICT tools in disseminating information to learners. Mobile-learning is gaining recognition in teaching and learning process today. It facilitates teaching and learning process by easing tasks of both teachers and learners . Therefore, this study examined the perceptions of students on the need for the development of mobile-learning model for teaching Arabic reading skills to non-Arab speakers. A total of 120 international students were randomly selected for this study from the Institute of Arabic Language for Non-Arab Speakers, King Saud University, Riyadh, Kingdom of Saudi Arabia. It used descriptive statistics like simple percent- age, mean and standard deviation to analyze the data collected from respondents. The result of the findings revealed that there is need to improve Arabic reading pro- ficiency and the current reading activities of non-Arab speakers in King Saud Uni- versity. These show that the mobile-learning device will be highly needed in doing these. It was also found that students expected performance, effort, will improve with the use of mobile-learning devices. Students are ready to turn-up good attitude towards teaching and learning if mobile devices are used for the instruction. This will also enhance their social development and increase their self-efficacy. There- fore, management of the University must strive to provide adequate facilitates for mobile-learning, train teachers and students on the usage and motivate them towards using it in their instruction process.